Variability and differences of growth vigour in the set of 36 genotypes of apricot (Prunus armeniaca L.). - Vachim, Z. (International Journal of Horticultural Science, 2001)
Growth vigour of 36 apricot cultivars and new hybrids grafted on apricot seedling rootstock (Prunus armeniaca L.) was evaluated on the base of measurements of stem girth from the 411' to the 10th year after planting. There were differences in growth vigour of genotypes under study. In the evaluated set of genotypes the control cultivar 'Veecor may be classified as a genotype with below-average growth vigour. Only four genotypes (-Reale d'Imola-, Sanagian -Moldavskii krupnoplodnyl and 'LE-2385') were found with significantly higher growth vigour than that of control cultivar 'Veecot' in years of the end of experimental period. Two genotypes (Farmingdale', -LE-SE0-24') were found with significantly higher growth vigour only at the beginning of experimental period and one cultivar ('Vivagold-) with significantly lower growth vigour in the first four years. Genotypes with different growth vigour can be used in further breeding programmes and/or as components inhibiting or supporting the growth in indirect vegetative propagation. Within the whole experimental period, the rank of growth vigour of genotypes practically did not change. This was demonstrated by highly significant or significant coefficients of correlation existing between individual pairs of years (r=0.32+ to r=0.96++). As far as the time difference between years in individual pairs of years was higher, the correlation coefficients were lower. In individual years, variability of growth vigour was relatively low and ranged from 9.83 to 13.64%.